2023
DOI: 10.1007/s10067-023-06670-0
|View full text |Cite|
|
Sign up to set email alerts
|

Incident autoimmune diseases in association with SARS-CoV-2 infection: a matched cohort study

Abstract: Objectives To investigate whether the risk of developing an incident autoimmune disease is increased in patients with prior COVID-19 disease compared to those without COVID-19, a large cohort study was conducted. Method A cohort was selected from German routine health care data. Based on documented diagnoses, we identified individuals with polymerase chain reaction (PCR)-confirmed COVID-19 through December 31, 2020. Patients were matched 1:3 to control … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…These findings are almost consistent with those of previous studies. 20,21 Remarkably, we observed a persistent risk for many autoimmune diseases. For certain diseases, such as IgG4RD and SSc, the risk was observed to be even higher in the later period (day 391-∞) compared with the earlier period.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…These findings are almost consistent with those of previous studies. 20,21 Remarkably, we observed a persistent risk for many autoimmune diseases. For certain diseases, such as IgG4RD and SSc, the risk was observed to be even higher in the later period (day 391-∞) compared with the earlier period.…”
Section: Discussionmentioning
confidence: 77%
“…A recent study demonstrated that the outpatient setting was associated with a higher risk of developing autoimmune diseases than the inpatient setting, 20 whereas another study showed that hospitalization and intensive care were associated with a higher risk of autoimmune diseases associated with COVID-19. 21 They investigated the effect of COVID-19 compared with non-COVID-19 patients using subgroup analysis, such as inpatients or outpatients. In the non-COVID-19 group, the reasons for hospitalization were likely to be variable and may be associated with symptoms resulting from the preclinical stages of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analyses stratified by race indicated that White patients generally exhibited a higher risk than Asian patients, except for SLE . Another study assessing the incidence of autoimmune diseases after COVID-19 in the German population also observed an elevated risk within the COVID-19 cohort (first onset of autoimmune disease incidence rate ratio, 1.43; 95% CI, 1.37-1.48). Given that our study primarily included Asian participants, we hypothesize that their estimated risks were lower, or may appear to be lower, as a result of delayed disease development or progression, compared with those observed in other ethnic groups.…”
Section: Discussionmentioning
confidence: 95%
“…In this cohort study, we comprehensively examined and compared the risks of autoimmune and autoinflammatory connective tissue disorders in COVID-19 and control cohorts. Several previous reports have evaluated the incidence of autoimmune diseases following COVID-19 . One large cohort study using a global COVID-19 data set found that the COVID-19 group had a higher risk of various autoimmune diseases compared with a control group.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chang et al 28 analyzed data from an extensive global COVID‐19 database and found an increased risk of SLE (adjusted hazard ratio [HR] 2.98; 95% CI 2.78–3.20) among 887 455 individuals with COVID‐19 compared to non‐COVID‐19 individuals during a 6‐month follow‐up period. However, another study by Tesch et al 29 examined a cohort of 640 701 non‐vaccinated individuals with polymerase chain reaction‐confirmed COVID‐19 in 2020 and reported an incidence rate ratio of 1.35 (95% CI 0.92–1.95) for developing SLE between 3 and 15 months after SARS‐CoV‐2 infection. Therefore, most SLE cases emerge during or shortly after the acute phase of SARS‐CoV‐2 infection, suggesting the involvement of specific pathogenic mechanisms.…”
Section: Figurementioning
confidence: 99%